(untitled) (Research, Society and Development, 2023)
Pereskia aculeata, a plant popularly known as ora-pro-nobis, fits the concept of Non-Conventional Food Plant (PANC). The objective of this work was to obtain flour and protein concentrates from ora-pro-nobis leaves, evaluating some physical-chemical characteristics with technological and nutritional relevance. A flour was elaborated and four treatments were tested for protein concentration: domestic concentration (CD), thermo coagulation (TC), acid coagulation (CA) and acid thermo coagulation (TCA). Products were evaluated for color, yield, protein content, protein recovery and antioxidant capacity. The flour had lighter, green and yellower hue than the concentrates, which differed from each other in luminosity and in the a* attribute. The CD yield was lower in relation to the other concentrates, but this treatment had a higher protein content (31.68%), more than twice as much as the flour (15.14%) and higher than TC, CA and TCA treatments, with mean values of 26.25; 27.37 and 24.12%, respectively. The TC, CA and TCA treatments had the highest protein recovery, with respective averages of 61.05; 62.85 and 54.61%, in relation to the CD (34.48%). The flour showed a higher antioxidant capacity than the concentrates, among which TCA had a higher antioxidant capacity, that is, the concentrations resulted in losses of ora-pro-nobis bioactive compounds. It is concluded that the treatments to concentrate the protein were successful, however, the yield, protein content and protein recovery were not high, in addition to becoming darker, less green and losing antioxidant capacity, which represents a disadvantage in relation to the ora-pro-nobis flour.